Chapter 9 (The Economics of) Cultural Festivals in the Digital Age An Analysis of the Comics Publishing Industry - Salvador, Elisa (Taylor & Francis, 2022)
book fairs, creative industries, cultural effects, digital age, food events, management, music festivals, organization, publishing, strategy, UNESCO heritage, Venice Biennale